2016
DOI: 10.1186/s13027-016-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Variability of high risk HPV genotypes among HIV infected women in Mwanza, Tanzania- the need for evaluation of current vaccine effectiveness in developing countries

Abstract: BackgroundHigh risk (HR) human papilloma Virus (HPV) genotypes have been associated with cervical cancer. In Tanzania there is a limited data on the epidemiology of HPV and genotypes distribution among HIV infected women. Here we document varieties of HPV genotypes associated with cervical squamous intraepithelial lesions (SIL) among HIV- infected women at Bugando Medical Centre, Mwanza-Tanzania.MethodsA cross sectional hospital based study involving HIV infected women was conducted between August and October,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
6
6
0
Order By: Relevance
“…These findings highlighted that the HPV prevalence in the HIVpositive Moroccan women was significantly higher than observed in the general population (15.7%-43.1%) [6][7][8]. This seems to be in line with other previous reports which documents high proportion of HIVinfected women carrying varieties of HR-HPV types [27,28]. Furthermore, previous reports showed that HIV-infected women had a seven-fold increased rate of persistence of HR-HPV [29].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These findings highlighted that the HPV prevalence in the HIVpositive Moroccan women was significantly higher than observed in the general population (15.7%-43.1%) [6][7][8]. This seems to be in line with other previous reports which documents high proportion of HIVinfected women carrying varieties of HR-HPV types [27,28]. Furthermore, previous reports showed that HIV-infected women had a seven-fold increased rate of persistence of HR-HPV [29].…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, previous reports showed that HIV-infected women had a seven-fold increased rate of persistence of HR-HPV [29]. In addition, high HPV infection prevalence in HIV-positive women has been reported in Italy (44%) [30], US (54%-73%) [31], Brazil (48-78.8%) [32][33][34][35], South Africa (52.4%-74%) [36,37], Tanzania (54.1%) [27]and Burkina Faso (66.1%) [38]. However, a preliminary study carried out among 87 HIV-positive women in the Souss region (South of Morocco) reported a prevalence (39.3%) less than observed in our study [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,28 An example of this association is the crosssectional study conducted by Mujuni et al, which evaluated 255 HIV-positive women and showed the presence of HPVpositive DNA in about 54% of patients, with high-risk HPV genotypes present in 48.6% of patients, culminating in a higher incidence of HPV positivity in patients with CD4 levels below 100 and the presence of intraepithelial lesions. 29 Our study also demonstrated the HPV genotype coverage inside the available vaccines. Although HIV-positive people generally show infection with multiple forms of HPV, we found that of 26 patients with genotypes identified, 23 (88.4%) and 25 (96.1%) of them had at least one genotype included in 4vHPV and 9vHPV, respectively.…”
Section: Discussionsupporting
confidence: 58%
“… 29 The prevalence of specific high-risk HPV types such as HPV-52, HPV-58, HPV-35, and HPV-16 in HIV-positive women is itself a predictor for cervical disease that can be assessed through genotyping. 58 Other studies have evaluated the use of alternative triage methods for HPV-positive women. One of these is the identification of E6 protein because real-time nucleic acid sequence-based amplification has proven to allow type-specific detection of E6 mRNA from high-risk HPV types.…”
Section: Overview Of the Current Screening Strategies And Issuesmentioning
confidence: 99%